Lin28b-let-7 Modulates mRNA Expression of GnRH1 Through Multiple Signaling Pathways Related to Glycolysis in GT1-7 Cells - Yujing Xie; Xin Li; Meng Wang; Mingxing Chu; Guiling Cao (Animals)
Lin28b and let-7 miRNA regulate mammalian pubertal initiation and Gonadotropin-releasing hormone (GnRH) production. However, it remains unclear which signaling pathways Lin28b regulates to modulate GnRH production. In this study, the mRNA expression levels of Lin28b and let-7 in the pubertal and juvenile goat hypothalamus and pituitary gland were detected, and Lin28b expression in the pubertal hypothalamus decreased significantly compared with that in juvenile tissues. It was predicted that Lin28b might inhibit GnRH1 expression, which was verified in the GnRH-producing cell model GT1-7 cells. Lin28b inhibited GnRH1 expression and promoted Kiss1/Gpr54 signaling. The pyruvate content and the expression of Hif1a and Hk2, which were related to glycolysis, were also promoted by Lin28b overexpression. Additionally, 77 differentially expressed miRNAs (DEMIs) in Lin28b-overexpressed GT1-7 cells were identified. Bioinformatics analysis and mRNA expression of the target genes of DEMIs revealed that the MAPK and PI3K-AKT-mTOR signaling pathways were key pathways that involved the regulatory effect of Lin28b on GnRH. In GT1-7 cells, GnRH1 expression was suppressed by blocking mTOR signaling with rapamycin, which was rescued by Lin28b overexpression. These results indicate that Lin28b-let-7 regulates GnRH1 expression through several pathways, including the Kiss1/Gpr54, MAPK, and mTOR signaling pathways, which are all related to glucose metabolism and provide new insights into the molecular mechanism of the regulatory role of Lin28b on GnRH production.